Self-Defence and the Principle of Non-Combatant Immunity - Frowe, Helen (Journal of moral philosophy, 2011)
The reductivist view of war holds that the moral rules of killing in war can be reduced to the moral rules that govern killing between individuals. Noam Zohar objects to reductivism on the grounds that the account of individual self-defence that best supports the rules of war will inadvertently sanction terrorist killings of non-combatants. I argue that even an extended account of self-defence—that is, an account that permits killing at least some innocent people to save one’s own life—can support a prohibition on terrorism, provided that it distinguishes between direct and indirect threats. What such an account cannot support is the blanket immunity of non-combatants to defensive killing. If a non-combatant is morally responsible for indirectly threatening in an unjust war, she can be liable to defensive killing. However, this gives us reason to revise our account of permissible killing in war, rather than to reject the reductivist account.